2018
DOI: 10.5888/pcd15.180053
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutrition Habits and Reducing Sedentary Time Among Preschool-Aged Children in Cuenca, Ecuador: A Trial of a School-Based Intervention

Abstract: IntroductionIn Ecuador, the prevalence of overweight and obesity among school-age children is more than triple that of preschool-age children; however, preschoolers have not been the target of interventions.MethodsWe developed an educational and behavioral intervention that included games, singing, and storytelling. Children were recruited from municipal preschools in Cuenca and were enrolled in the pilot intervention (PI) (N=155) for the 2015–2016 school year, which consisted of a 3-month in-school program. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 23 publications
1
29
0
5
Order By: Relevance
“…After all rounds of screening, 39 articles were identified and included. Eight additional studies were identified by hand searching references of included articles and other relevant articles, resulting in 47 articles that met the inclusion criteria and were included in the systematic review . Of these 47 studies, 24 studies could be included in the meta‐analysis because they had a controlled design and measured water consumption in an amount or frequency …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After all rounds of screening, 39 articles were identified and included. Eight additional studies were identified by hand searching references of included articles and other relevant articles, resulting in 47 articles that met the inclusion criteria and were included in the systematic review . Of these 47 studies, 24 studies could be included in the meta‐analysis because they had a controlled design and measured water consumption in an amount or frequency …”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 studies, the majority were based in the United States (24/47) or in Europe (14/47) . All studies were published after 2000, and most (40/47) were published in or after 2010. Most studies were RCTs (24/47); other designs were non‐RCTs (9/47), repeated cross‐sectional controlled (1/47), or noncontrolled quasi‐experimental study designs (13/47) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations